2022
DOI: 10.21203/rs.3.rs-1094583/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of the Animated Video Method in Vocabulary Learning: A Case Study of Noble Technical Institute in Arbil

Abstract: This research evaluates the effectiveness of animated videos in vocabulary learning among Noble Technical Institute (NTI) students. Experimental research methodology was used with 40 students as the study subject, and the study subjects were picked randomly. After the pre-test was conducted for all the students, they were grouped into two categories for the treatment regime: those taught with animated video and the rest without animated video. Post-test was conducted after the lesson. The data were analyzed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…They also increase learners' motivation and create mental images that enhance recall and retention of vocabulary learnt. Moreover, Ridha, et al (2022) indicated that teaching vocabulary using animated videos demonstrate significant gains in vocabulary mastery and make the learning process interesting and more productive.…”
Section: Introductionmentioning
confidence: 99%
“…They also increase learners' motivation and create mental images that enhance recall and retention of vocabulary learnt. Moreover, Ridha, et al (2022) indicated that teaching vocabulary using animated videos demonstrate significant gains in vocabulary mastery and make the learning process interesting and more productive.…”
Section: Introductionmentioning
confidence: 99%